(3Jbjje GdGeJMGf GdQSej aj eGOI GdadSaI GdYGeI Hjf GdfehPLjf GdJbdjOj hGdEfJGLj(B((3daQhY GdELJeGY EbJUGO hGdYdhe GdYGqeI hYdhe GdMjGI(B)s - (3LqaGd, ajcJhQjG SYjOs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2015)
(3JMGhd GdOQGSI Jbjje WHjYI CSFdI GdGeJMGfGJ GdQSejI GdeWQhMI aj eGOI GdadSaI GdYGeI, heYQaI eOi JhGabgG eY GdefgL GdOQGSj GdeYJeO hJMOjO GdKZQGJ hGdThGFH GdJj JYJQjgG, hGdcTa Yf GdeYGjjQ GdJj jLQj GdESJfGO EdjgG YfO hVYgG, hWGHYgG GdeYQaj(B- (3GdhXjaj GdYGe(B. (3HGdEVGaI Edi JMOjO fbGW GdVYa hGdbhI aj JWHjb GdJbjje HGdcaGjGJ aj gPg GdeGOI, hGdcTa Yf hXjaI GdEeJMGf GdQSej dJHjGf eSJhi JMbjb GdcaGjGJ GdeQLhI efg(B. (3EYJeOJ GdOQGSI GdefgL GdhUaj GdJMdjdj, hoLeYJ GdeYdheGJ ef NdGd GSJHjGfGJ hLgJ ddCSGJPI HTcd YThGFj ef bWGYj GdJYdje GdQSej hGdNGU, dJbjje CSFdI GdEeJMGfGJ GdQSejI aj eGOI GdadSaI GdYGeI dUaha GdGLJeGY hGdGbJUGO, Ydhe GdMjGI, hGdYdhe GdYGeI, Hjf GdfehPLjf GdJbdjOj hGdEfJGLj(B. (3ceG JeJ ebGQHI eVGejf GdcJGH hGdefgL heOi edGAeJgG ddCgOGa hEfYcGSgG Ydi CSFdI GdGeJMGfGJ GdQSejI hWGHYgG GdfeWj GdecQQ, GdeWQhMI aj GdcJGH GdeOQSj GdQSej hGdNGU(B. (3HjfJ fJGFL GdOQGSI hLhO eTcdGJ eJYdbI HGdcJGH GdeOQSj, GdefgL, WQb JOQjS eGOI GdadSaI, CSGdjH JbjjegG, hfRYI GSJfSGHjI eRGLjI aj GdJUMjM(B. (3XgQ JCKjQ GdNHQI GdJUMjMjI hGdJYdjejI hGdeSJhi GdCcGOjej deUMM eGOI GdadSaI Ydi YedjI Jbjje eGOI GdadSaI aj GdEeJMGfGJ GdQSejI, ceG JHjf Cf bhI GdeDKQGJ GdHjFjI, GdacQjI, hGdNHQI jecf Cf JThT Ydi YedjI GdJbjje aj GdeGOI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Cycle Secondaire L$1 (Benseignement de la Philosophie et la Morale Examens Officielss; Secondary Education Philosophy and Moral Education Official Exams; (3GdeQMdI GdKGfhjI JYdje GdadSaI hGdGNdGb GdGeJMGfGJ GdQSejIs